Toll-like Receptor 7 and TLR9 Dictate Autoantibody Specificity and Have Opposing Inflammatory and Regulatory Roles in a Murine Model of Lupus - Christensen, Sean R.; Shupe, Jonathan; Nickerson, Kevin; Kashgarian, Michael; Flavell, Richard A.; Shlomchik, Mark J. (Immunity (Cambridge, Mass.), 2006)
Antibodies (Abs) to RNA- and DNA-containing autoantigens are characteristic of systemic lupus erythematosus (SLE). We showed previously that Toll-like receptor (TLR) 9, recognizing DNA, is required for the spontaneous generation of DNA autoantibodies, but not for the development of lupus nephritis in susceptible mice. We report that lupus-prone mice deficient in TLR7, a receptor for ssRNA, failed to generate Abs to RNA-containing antigens (Ags) such as Smith (Sm) Ag. TLR9 and TLR7 also had dramatic effects on clinical disease in lupus-prone mice. In the absence of TLR9, autoimmune disease was exacerbated, lymphocytes and plasmacytoid DCs were more activated, and serum IgG and IFN-α were increased. In contrast, TLR7-deficient mice had ameliorated disease, decreased lymphocyte activation, and decreased serum IgG. These findings reveal opposing inflammatory and regulatory roles for TLR7 and TLR9, despite similar tissue expression and signaling pathways. These results have important implications for TLR-directed therapy of autoimmune disease.